Effect of discussion and deliberation on the public's views of priority setting in health care: focus group study. Issue 7188 (3rd April 1999) - Dolan, Paul; Cookson, Richard; Ferguson, Brian
Abstract: Objective : To investigate the extent to which people change their views about priority setting in health care as a result of discussion and deliberation. Design : A random sample of patients from two urban general practices was invited to attend two focus group meetings, a fortnight apart. Setting : North Yorkshire Health Authority. Subjects : 60 randomly chosen patients meeting in 10 ugroups of five to seven people. Main outcome measures : Differences between people's views at the start of the first meeting and at the end of the second meeting, after they have had an opportunity for discussion and deliberation, measured by questionnaires at the start of the first meeting and the end of the second meeting. Results : Respondents became more reticent about the role that their views should play in determining priorities and more sympathetic to the role that healthcare managers play. About a half of respondents initially wanted to give lower priority to smokers, heavy drinkers, and illegal drug users, but after discussion many no longer wished to discriminate against these people. Conclusion : The public's views about setting priorities in health care are systematically different when they have been given an opportunity to discuss the issues. If the considered opinions of the general public are required, surveys that do not allow respondents time or opportunity for reflection may be of doubtful value.